An Innovative Way to Produce γ‐TiAl Blades: Spark Plasma Sinteringa. Issue 10 (7th April 2015) - Voisin, Thomas; Monchoux, Jean‐Philippe; Durand, Lise; Karnatak, Nikhil; Thomas, Marc; Couret, Alain
<x xml:space="preserve">Abstract</x> In this Communication, it is shown that the production of turbine blades in γ‐TiAl alloys through Spark Plasma Sintering (SPS) is a viable manufacturing route, by demonstrating that near‐net shaping of γ‐TiAl blades is successful, and by developing an alloy with balanced and outstanding mechanical properties at room and high temperatures in a single run and without subsequent thermal treatments.